Hubungan Kekerabatan Padi dan Mutu Beras Gogo Aksesi Lokal Bangka Barat: Genetic Relationship and Rice Quality of Upland Rice Local Accessions from West Bangka Regency - Amilia, Rossa; Mustikarini, Eries Dyah; Zasari, Maera (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Genetic diversity of local rice is important for food security and sustainable agriculture. Local rice excels in resistance to biotic and abiotic stresses, short harvest periods, and cost efficiency, making it a favorable choice for farmers and consumers. This research aims to analyze the genetic relationships, rice organoleptic properties, and chemical characteristics of several upland rice local accessions in West Bangka Regency. This study used a field survey method with purposive random sampling technique. Samples were collected for 34 quantitative and qualitative characters. Chemical property testing included moisture content, ash, fat, protein, carbohydrate, lignin, amylose, and anthocyanin, as well as organoleptic testing. Data analysis used NTSys and DSSASTAT software. The genetic relationship based on qualitative characters was divided into two clusters at a 61% coefficient, and the closest genetic relationship was found between Jawa and Mayang accessions with a 100% coefficient. Lignin content ranged from 0.62-0.79%, amylose from 8.14-18.64%, and anthocyanin from 0.04-2.54%, varying among accessions. Variations in moisture content were 11.63-13.13%, ash 0.34-0.59%, fat 0.12-0.78%, protein 7.42-8.92%, and carbohydrates 77.84-80.28%. Organoleptic tests showed that the Pulut Emas accession received the highest overall rating of 3.68.